Status Quo and Inequalities of the Statutory Provision for Young Children in England, 40 Years on From Warnock - Castro-Kemp, Susana; Palikara, Olympia; Grande, Catarina (Frontiers in Education, 2019)
In England, the Children and Families Act 2014 has been regarded as the most radical change in the Special Educational Needs and Disability provision for decades. Building on the recommendations of the Warnock report and subsequent 1981 Education Act, the 2014 Act introduced the Education Health and Care plans to replace the Statements of Special Educational Needs, with the view to promote holistic and participation-focused provision. This study aimed to examine and compare the quality of the Education Health and Care plans developed in some of the most deprived and some of the most affluent regions in England, with a particular focus on young children, given the well documented instrumental role of early childhood intervention. The Education Health and Care plans of 71 children aged 4 to 8 years old were gathered and a systematic analysis of the needs and outcomes reported in those plans was conducted. Results show that the pattern of needs is similar across diagnostic categories, with the exception of mobility needs. However, more affluent local authorities provide more detailed descriptions of certain types of needs (related to mental functions and sensory functions) and higher quality outcomes. Special settings also present more detailed descriptions of some needs than mainstream settings, as well as higher quality outcomes. The higher the number of reported mental functions needs (related to emotional regulation), the higher the quality of the outcomes written for those children. However, the quality of the outcomes is markedly low across plans, local authorities and settings. These results show that the status quo of the Special Educational Needs and Disability policy and provision is still characterised by marked social inequality and specialised work-force disparities, 40 years on from the first Warnock report and the commitment to full inclusion.